2010
DOI: 10.1177/0265407510375261
|View full text |Cite
|
Sign up to set email alerts
|

Shyness and online social networking services

Abstract: Online social networking services are Internet websites that allow individuals to learn about and communicate with others. This study investigated the association between use of these websites and friendship quality for individuals varying in shyness. Participants (N = 241) completed questionnaires assessing their use of Facebook, an online social networking service, shyness, perceived available social support, loneliness, and friendship quality. Results indicated an interaction between shyness and Facebook us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(92 citation statements)
references
References 49 publications
6
86
0
Order By: Relevance
“…The measure has been administered online in full (Baker & Oswald, 2010) and abbreviated (Hollenbaugh, 2011) versions and…”
Section: Discussionmentioning
confidence: 99%
“…The measure has been administered online in full (Baker & Oswald, 2010) and abbreviated (Hollenbaugh, 2011) versions and…”
Section: Discussionmentioning
confidence: 99%
“…In real life, shy people avoid communicating with others because they feel they lack social skills (Baker & Oswald, 2010). Due to this, they are more sensitive to the non-verbal cues that their conversational partners provide.…”
Section: Online Social Enhancementmentioning
confidence: 99%
“…Shy or socially anxious people also prefer communicating online, as the slow and asynchronous nature of text-based communication allows them to take their time to think about responses (Baker & Oswald, 2010;Caplan, 2002). As such, they feel greater levels of social control online than they do in face-to-face interactions.…”
Section: Online Social Enhancementmentioning
confidence: 99%
“…Indeed, social media use can provide positive benefits for users, including increased social capital (N. Ellison, Steinfield, & Lampe, 2006;Nicole B. Ellison et al, 2011;Lambert, 2016). In addition, Baker and Oswald (2010) found that using social media increased perceptions of friendship quality and provided social support for people who were shy.…”
Section: Peer Group Identificationmentioning
confidence: 99%
“…Social media use has been found to have both negative (Clayton, Nagurney, et al, 2013;Clayton, Osborne, Miller, & Oberle, 2013;Mod, 2010;Muise, Christofides, & Desmarais, 2009;Rahaman, 2015) and positive impacts on users' relations to others (Baker & Oswald, 2010;. In contrast, a recent American study found that internet use had no impact on relationships for more than 60% of respondents (Pew Research Center, 2014).…”
Section: Introductionmentioning
confidence: 99%